Safety and diagnostic performance of dual-source CT scan in comparison with single source CT scan and conventional angiography in coronary heart diseases - M Mokhtari Payam; A akbari Sari; MR Aye; M Mobinizadeh; S Manavi (Tehran University of Medical Sciences, 2010)
Background: The aim of this study is to explore the safety and diagnostic performance of dual-source CT scan in comparison with single source CT scan and conventional angiography in patients with coronary heart diseases.Materials and methods: A systematic review was performed using CRD standard methods. The Cochrane Library, MEDLINE, EMBASE، Google Scholar and TRIP were searched up to April 2009. The references of the marked studies and gray literature were also searched. Results: 17 articles were included. 9 articles reported the safety and 12 articles reported the diagnostic performance of DSCT.  Generally DSCT was a non-invasive and safe procedure.  Using DSCT the exposure of patient to X-ray was less than 64-slice single source CT (SSCT) and more than conventional angiography. For the DSCT the mean sensitivity was 90.4%, mean specificity was 82%, mean PPV was 83% and mean NPV was 96%. For the SSCT the mean sensitivity was 90.4%, mean specificity was 82%, mean PPV was 83% and mean NPV was 96%. The mean sensitivity, specificity, PPV and NPV of DSCT were slightly higher than SSCT. Conclusion: DSCT is a noninvasive and relatively safe technology. The diagnostic performance of DSCT is higher than SSCT, but its performance is not so much high to be able to substitute the conventional invasive angiography which is still the gold standard test.